Analysis of Uranyl Carbonate Complexes in an Open and Close Environmental System by Analytical Chemistry - Sahat Simbolon (Widyanuklida, 2000)
ABSTRACT Variation of C032- ion concentration from CO2 gas originated from atmosphere, in natural water in an open and close system versus pH of the solution is described. Reaction between U022+ cation with CO32- anion is also described by using calculation, comparison of each species of uranyl carbonate complexes to its total values. Each mol fraction of uranyl corbonate complex versus pH of the solution is calculated using Lotus 123 release 2.4. It is found that uranyl carbonate complexes species in natural water which is slightly acid in an open system is simpler than that in a close system. On the other hand, uranil carbonate complexes species in natural water which is slightly base is simpler in an open system than that in a close system. ABSTRAK Diterangkan perubahan konsentrasi ion CO32- di dalam air alam pada lingkungan terbuka dan tertutup berasal dari gas CO2 yang terdapat di udara terhadap pH larutan. Reaksi antara kation UO22+ dengan anion CO32- juga diterangkan dengan menggunakan perhitungan, perbandingan antara masing-masing spesies kompleks uranil karbonat terhadap nilai totalnya. Perangkat lunak Lotus 123 release 2.4 digunakan untuk menghitung masing-masing molfraksi dari masing-masing spesies uranil karbonat terhadap pH larutan. Didapatkan bahwa spesies kompleks uranil karbonat di dalam air alam pada lingkungan terbuka pada kondisi asam lebih sederhana dibandingkan dengan di dalam air alam pada lingkungan tertutup. Sebaliknya kompleks uranil karbonat di dalam air pada lingkungan terbuka dan dalam suasana basa kandungannya lebih sederhana daripada di dalam air alam pada lingkungan tertutup.